Band structure of [100] surface of Cd₁₋x Mn x Te diluted magnetic semiconductor - Melnichuk, S.V.; Mikhailevsky, Y.M.; Rarenko, I.M.; Yurijchuk, I.M. (Condensed Matter Physics, 2000)
Electronic band structure of the diluted magnetic semiconductor Cd₁₋x Mn x Te [100] ideal surface is calculated by the semiempirical tight- binding method in the framework of sps*-model. Surface bands, emerging above the bulk band structure, as well as their type, energy position and localization near the parting border with vacuum are investigated. It is shown that Mn 3d-states as well as sp-states play appreciable role in the formation of surface bands. The peculiarities of surface band structure are analyzed in the dependence of solid solution composition.